Variable power supply (wind power system) / Che Ku Mohd Faiz Che Ku Abdullah and Khairul Afshah Basaruddin - Che Ku Abdullah, Che Ku Mohd Faiz; Basaruddin, Khairul Afshah (2005)
As we known, the population of human was increase greatly nowadays. The increasing of population means that the demand for energy is greater year by years. But, most of energy that we use nowadays is not renewable energy and it was decrease and may be finish in a short time. So, from now we must have the alternative energy that will support the demand of human. Wind is a form of solar energy. Winds are caused by the uneven heating of the atmosphere by the sun, the irregularities of the earth's surface, and rotation of the earth. Wind flow patterns are modified by the earth's terrain, bodies of water, and vegetation. Humans use this wind flow, or motion energy, for many purposes: sailing, flying a kite, and even generating electricity. The terms wind energy or wind power describes the process by which the wind is used to generate mechanical power or electricity. Wind turbines convert the kinetic energy in the wind into mechanical power. This mechanical power can be used for specific tasks (such as grinding grain or pumping water) or a generator can convert this mechanical power into electricity.